2015
DOI: 10.18632/oncotarget.6006
|View full text |Cite|
|
Sign up to set email alerts
|

γKlotho is a novel marker and cell survival factor in a subset of triple negative breast cancers

Abstract: Over the last decade, breast cancer mortality has declined. However, triple negative breast cancer (TNBC) remains a challenging problem mostly due to early recurrence and lack of molecularly driven treatments. There is a critical need to identify subgroups of TNBC with common molecular features that can be therapeutically targeted. Here we show that in contrast to Klotho and βKlotho, the third member of the Klotho protein family, γKlotho, is overexpressed in more than 60% of TNBCs and correlates with poorer di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 74 publications
2
31
1
Order By: Relevance
“…Trošt et al . showed that, in patients with triple negative breast cancer, the expression level of KLγ was high and correlates with poor progression, that KLγ was a necessary factor for cell survival, and that depletion of KLγ resulted in cell cycle arrest, apoptosis, and persistent activation of the ERK1/2 signaling pathway [ 22 ]. Therefore, we hypothesize that KLγ plays a role in the promotion of bladder cancer and that the balance of existing KLs affects downstream signaling, including that of FGF and FGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trošt et al . showed that, in patients with triple negative breast cancer, the expression level of KLγ was high and correlates with poor progression, that KLγ was a necessary factor for cell survival, and that depletion of KLγ resulted in cell cycle arrest, apoptosis, and persistent activation of the ERK1/2 signaling pathway [ 22 ]. Therefore, we hypothesize that KLγ plays a role in the promotion of bladder cancer and that the balance of existing KLs affects downstream signaling, including that of FGF and FGFR.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to KLγ, there are fewer reports about the association between KLγ and cancer. Previous reports showed that KLγ has an important role in the cell proliferation ability of colon cancer and the expression level of KLγ was associated with prognosis in triple negative breast cancer [ 21 , 22 ]. In the present study, we focused on the clinical significance of KLγ, which could be a regulator of cancer progression for UCB.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there are only three reports on the association between KLG and cancer development (9,23,24). The present study is the first report of the relationship between KLG and prostate cancer.…”
Section: Discussionmentioning
confidence: 50%
“…Kim et al reported that KLG is an important factor in cell proliferation by activating ERK1/2 signaling pathway in colon cancer (9). Trošt et al reported that high expression level of KLG correlates with poor disease progression and that in vitro analysis indicated that KLG was a necessary factor for cell survival; depletion of KLG resulted in cell cycle arrest, apoptosis, and persistent activation of the ERK1/2 signaling pathway in patients with triple-negative breast cancer (24). Therefore, we speculate that KLG plays a role in the promotion of prostate cancer growth and that the balance of existing KLs affects activation of various pathways, including FGF/FGFR signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation